2007
DOI: 10.1080/02652040601058525
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of microcapsules with self-microemulsifying core by a vibrating nozzle method

Abstract: Incorporation of drugs in self-microemulsifying systems (SMES) offers several advantages for their delivery, the main one being faster drug dissolution and absorption. Formulation of SMES in solid dosage forms can be difficult and, to date, most SMES are applied in liquid dosage form or soft gelatin capsules. This study has explored the incorporation of SMES in microcapsules, which could then be used for formulation of solid dosage forms. An Inotech IE-50 R encapsulator equipped with a concentric nozzle was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…When CaCl 2 was added to SMES in higher amounts the microencapsulation process was disabled by clogging of the nozzle. A similar effect was observed previously (Homar et al, 2007).…”
Section: Optimization Of Self-microemulsifying Coresupporting
confidence: 87%
See 2 more Smart Citations
“…When CaCl 2 was added to SMES in higher amounts the microencapsulation process was disabled by clogging of the nozzle. A similar effect was observed previously (Homar et al, 2007).…”
Section: Optimization Of Self-microemulsifying Coresupporting
confidence: 87%
“…The qualitative composition of SMES was selected on the basis of our previous work (Špiclin et al, 2003;Homar et al, 2007). SMES with different oil phase/surfactant ratios were tested to obtain the composition having the highest furosemide loading capacity (Fig.…”
Section: Determination Of Optimal Smes Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of EE%, high values were achieved for all NPs prepared due to the poor solubility of CB13 in the external aqueous phase, 24 and highest values were achieved using Resomer 502. Panyam et al 25 demonstrated that when hydrophobic drugs are used, NPs drug loading is closely matched with the respective solid-state drug-polymer solubility, that is, the ability of the polymeric matrix to entrap drug in the dispersed state.…”
Section: Drug Loadingmentioning
confidence: 94%
“…[11][12][13][14][15] Spray-drying has also been employed to formulate liquid SNEDDSs into free-flowing powders, using adsorbents such as Aerosil 200 16 and dextran. 17 Homar et al 18 and Zvonar et al 6 reported microencapsulation of liquid SNEDDSs to obtain solid powders of microcapsules. The powders containing liquid SNEDDS can be further formulated into solid dosage forms, such as tablets, capsules, and granules.…”
Section: Introductionmentioning
confidence: 99%